PENGGUNAAN MEDIA VIDEO BAHASA ARAB DALAM MENINGKATKAN MAHARAH AL-ISTIMA’ SISWA - Najmawati; Kaharuddin; Muhammad Irwan (IAIN Parepare, 2024)
This study aims to evaluate the effectiveness of using video media in enhancing the listening skills (maharah al-istima') of eighth-grade students at MTs Al-Amanah Waikaya. The specific objectives are to 1) assess the students' listening skills before the implementation of video media, 2) measure the students' listening skills after the use of video media, and 3) determine whether there is a significant improvement in listening skills following the use of video media. The research employs a quantitative approach with a pre-experimental design, using pre-test and post-test methods with a sample of 23 students. Data analysis was performed using inferential statistical tests via SPSS 26. The findings indicate a significant improvement in students' listening skills after the application of video media, with a Sig. (2-tailed) value of < 0.05 (0.000 < 0.05), confirming the research hypothesis. The implications of these findings suggest that video media can be an innovative and effective tool for teaching Arabic language skills. Recommendations include the routine integration of video media into the curriculum and training for educators to further enhance students' listening skills.